Nanomechanical and Thermophoretic Analyses of the Nucleotide-Dependent Interactions between the AAA(+) Subunits of Magnesium Chelatase - Adams, Nathan B. P. (J Am Chem Soc, 2016)
[Image: see text] In chlorophyll biosynthesis, the magnesium chelatase enzyme complex catalyzes the insertion of a Mg(2+) ion into protoporphyrin IX. Prior to this event, two of the three subunits, the AAA(+) proteins ChlI and ChlD, form a ChlID–MgATP complex. We used microscale thermophoresis to directly determine dissociation constants for the I-D subunits from Synechocystis, and to show that the formation of a ChlID–MgADP complex, mediated by the arginine finger and the sensor II domain on ChlD, is necessary for the assembly of the catalytically active ChlHID–MgATP complex. The N-terminal AAA(+) domain of ChlD is essential for complex formation, but some stability is preserved in the absence of the C-terminal integrin domain of ChlD, particularly if the intervening polyproline linker region is retained. Single molecule force spectroscopy (SMFS) was used to determine the factors that stabilize formation of the ChlID–MgADP complex at the single molecule level; ChlD was attached to an atomic force microscope (AFM) probe in two different orientations, and the ChlI subunits were tethered to a silica surface; the probability of subunits interacting more than doubled in the presence of MgADP, and we show that the N-terminal AAA(+) domain of ChlD mediates this process, in agreement with the microscale thermophoresis data. Analysis of the unbinding data revealed a most probable interaction force of around 109 pN for formation of single ChlID–MgADP complexes. These experiments provide a quantitative basis for understanding the assembly and function of the Mg chelatase complex.